Analgesic Nephropathy - Kingsley, D. P. E. (1972)
Sixty-six patients were seen from January 1963 to December 1970 in whom a diagnosis of analgesic nephropathy was made. The ratio of women to men was 2·7:1 and women presented at an earlier age. Over 60% of patients had or developed urinary tract infection and over one-third presented with serum urea levels over 300 mg/100 ml. Hypertension was present in 60% of patients and almost 20% had a history of peptic ulcer; hysterectomy had been done in 35% of the women. Most patients improved initially but more than half of those followed up died within five years of presentation. A direct relation was found between prognosis and the degree of functional renal impairment at presentation. Hypertension appeared to have an adverse effect on prognosis but no relation of prognosis to papillary necrosis, infection, or surgical procedures was found.